Prototipo técnico de vivienda agro-productiva rural por auto construcción en Vigía del Fuerte, Antioquia para la comunidad afro. Pro-Vi-Agro. (2022)
This research addresses the issue of housing deficit in rural populations of Colombia. The main problems of rurality that are related to housing such as poverty, lack of job opportunities, lack of education and inadequate implementation of materials, will be analyzed. Due to these problems, a quantitative and qualitative deficit related to basic housing needs is generated. The geographical delimitation of the study area is Vigia del Fuerte, Antioquia, since it is the municipality with the highest housing deficit in rural populations. The project seeks to improve the quality of life of this community through a housing prototype based on vernacular materials which have all the attributes and spatial qualities. A flexible and, especially, an economic construction system is proposed. At the same time this prototype could be adapted to the social, climatic and terrain conditions where all the culture, traditions and identity of the user will be linked. Therefore, the industrialized architecture is adjusted in vernacular modular systems as a solution to the housing deficit, besides to configuring the house as a unanimous integration of many of the environmental, architectural, and cultural characteristics of the place.